Finding our 'good way': critical reflections on researching disability, connection, and community from an Indigenous perspective. Issue 3 (4th May 2021) - Knudson, Sarah; Bird-Naytowhow, Kelley; Baldhead Pearl, Tamara
ABSTRACT: From our standpoints as Indigenous and ally researchers in the social sciences and socio-legal field, we offer an autoethnographic, reflexive account of a three-year research collaboration about close relationships, disability, and social connection. After engaging in one structured reflection exercise, several informal reflective conversations, and a pipe ceremony that marked the beginning of our next research endeavour together, we outline three emergent issues, each representing a point of struggle that ultimately became a strength in our research approach and contributions to knowledge. We also put forward a fourth issue that emerged in light of the COVID-19 pandemic and that has deeply shaped our research and reflection since. Our paper is intended to function as both a specific examination of lessons learned and knowledge generated in our experience of community-engaged Indigenous research, and also as a broader ensemble of principles that can be useful for doing thoughtful and critical reflective practice from an Indigenous perspective. We maintain that, taken together, the issues and principles we bring forth help to clarify how reflection on Indigenous research can assess whether and how we are doing our work in a 'good way, ' and exemplify an approach that strives to empower communities while generating new knowledge.